2010
DOI: 10.1111/j.1759-7714.2010.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 blockade enhances the anti-endothelial effect of radiation and inhibits irradiated tumor cell-induced migration of endothelial cells

Abstract: Background: EphA2 tyrosine kinase plays an important role in tumor angiogenesis, but whether targeting this pathway can affect response to ionizing radiation (IR) remains unknown. Methods: We investigated, using a soluble EphA2-Fc chimera, whether EphA2 inhibition could sensitize A549 and MCF-7 tumor cells, as well as human umbilical vein endothelial cells (HUVEC) and dermal microvascular endothelial cells (HDMEC), to IR. Results: EphA2-Fc resulted in a greater response of endothelial cells (EC) to IR than eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…The switch to a lymphangiogenic phenotype in tumors is likely to require up-regulation of expression of lymphangiogenic factors and down-regulation of expression of lymphangiogenic inhibitors (Alitalo and Carmeliet 2002). Genomic instability of tumor cells can lead to expression of multiple angiogenic and lymphangiogenic factors (Fokas 2010;Cao 2005). Members of the insulin-like growth factor (IGF) family are frequently expressed in many types of tumors associated with malignant progression and poor prognosis (Cullen et al 1990;Long et al 1998;Reinmuth et al 2002;Ritter et al 2002;Tanno et al 2001;Xie et al 1999).…”
Section: Introductionmentioning
confidence: 97%
“…The switch to a lymphangiogenic phenotype in tumors is likely to require up-regulation of expression of lymphangiogenic factors and down-regulation of expression of lymphangiogenic inhibitors (Alitalo and Carmeliet 2002). Genomic instability of tumor cells can lead to expression of multiple angiogenic and lymphangiogenic factors (Fokas 2010;Cao 2005). Members of the insulin-like growth factor (IGF) family are frequently expressed in many types of tumors associated with malignant progression and poor prognosis (Cullen et al 1990;Long et al 1998;Reinmuth et al 2002;Ritter et al 2002;Tanno et al 2001;Xie et al 1999).…”
Section: Introductionmentioning
confidence: 97%
“…A previous study found that up-regulated EphA2 expression is associated with cancer lymphogenous metastasis and poor prognosis, suggesting that EphA2 contributes to cancer progression ( 9 ). Moreover, EphA2 provides a protective mechanism by which tumors can attenuate irradiation-induced antivascular effect, so that the tumors can easily migrate and escape radiation ( 10 ). A previous literature represents EphA2 as an important target of miR-26b in gliomas ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…This evidence indicates that upregulation of EphA2 confers properties such as increased cancer motility, invasiveness, and metastasis. Furthermore, emerging evidence shows that EphA2 blockade enhances the antiendothelial effect of radiation and inhibits irradiated tumor cell‐induced migration of endothelial cells, implying that EphA2 probably gives cancer cells an opportunity to escape radiation stress [7].…”
Section: Introductionmentioning
confidence: 99%